Technical Analysis of Stock Investment Decisions in Telecommunication Companies Listed on the Indonesian Stock Exchange - Pasaribu, Marta KN (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine stock investment decisions in telecommunications companies listed on the Indonesia Stock Exchange using a technical analysis approach. This research does not use hypotheses, so quantitative descriptive research is used. The purposive sampling method was used to obtain a representative sample in accordance with the sampling criteria, namely telecommunications companies listed on the Indonesia Stock Exchange. The object of the research is data in the form of graphs and trends in monthly stock price movements of three issuers in the fourth quartile of 2023 starting from October-December 2023. The research results show that the analysis of the three stocks above shows that MACD crossovers often give false signals if they are not confirmed by indicator movements momentum like RSI. In the case of TLKM and ISAT, even though the MACD has crossed over, the RSI actually moves in the opposite direction or at least does not provide a strong response, so there is potential for a reversal. Likewise with EXCL where even though a MACD crossover occurred, the RSI did not penetrate a significant level to validate the signal. Overall, MACD crossovers without the support of evidence of changes in momentum from the RSI tend to be weak and inaccurate. It takes confirmation from other indicators for a MACD crossover to truly indicate a long-term trend change instead of just a high-risk temporary move. Thus, it is important to carry out multi-factor validation so that the MACD crossover signal is stronger before being used as a reference for entry or exit positions.